Factors Affecting Sharing on Social Media - รัตโน, ประภาภรณ์ (Journal of Roi Et Rajabhat University, 2016)
The objectives of this research were to study the relationship between personal factors and environmental factors towards sharing behavior in online social media and to study personal factors and environmental factors which influence sharing online. The research adopted the survey approach by using a questionnaire on the sample group, which included400students at Roi Et Rajabhat University. The results found most ofthesample used online social media 1–3 hours per day via smartphone, and their objective was information sharing. Most of thesample shares on Facebook, and the sample’s sharing online was at a medium levelwith image sharing at ahigh level. Results indicated that the personal factors of technology self– of technology self– of technology self efficacy, information self– efficacy, information self– efficacy, information self efficacy, social outcome expectations and sharing enjoyment correlated with sharing online while environmental factors correlating with sharing included social reference group, social context and type of social media. The personal factors of technology self– technology self– technology self efficacy and social outcome expectations were influential in sharing online, and the environmental factors of social reference group and type of social media were also influential in online sharing behavior. Moreover, results of this research found personal factors and environme environmental factors consist of social outcome expectations and expectations and that the type of social media is likewise likewise influential in sharing through social media.